A Stabilized, Monomeric, Receptor Binding Domain Elicits High-Titer Neutralizing Antibodies Against All SARS-CoV-2 Variants of Concern - Ahmed, Shahbaz; Khan, Mohammad Suhail; Gayathri, Savitha; Singh, Randhir; Kumar, Sahil; Patel, Unnatiben Rajeshbhai; Malladi, Sameer Kumar; Rajmani, Raju S.; van Vuren, Petrus Jansen; Riddell, Shane; Goldie, Sarah; Girish, Nidhi; et al. (Frontiers in Immunology, 2021)
Saturation suppressor mutagenesis was used to generate thermostable mutants of the SARS-CoV-2 Spike Receptor Binding Domain (RBD). A triple mutant with an increase in thermal melting temperature of ~7 ºC with respect to the wildtype B.1 RBD and was expressed in high yield in both mammalian cells and the microbial host, Pichia pastoris, was downselected for immunogenicity studies. An additional derivative with three additional mutations from the B.1.351 (beta) isolate were also introduced into this background. Lyophilized proteins were resistant to high temperature exposure and could be stored for over a month at 37 ºC. In mice and hamsters, squalene-in-water emulsion (SWE) adjuvanted formulations of the B.1 stabilized RBD were considerably more immunogenic than RBD lacking the stabilizing mutations and elicited antibodies that neutralized all four current variants of concern with similar neutralization titers. However, sera from mice immunized with the stabilized B.1.351 derivative showed significantly decreased neutralization titers exclusively against the B.1.617.2 (delta) VOC. A cocktail comprising of stabilized B.1 and B.1.351 RBDs elicited antibodies with qualitatively improved neutralization titers and breadth relative to those immunized solely with either immunogen. Immunized hamsters were protected from high dose viral challenge. Such vaccine formulations can be rapidly and cheaply produced, lack extraneous tags or additional components, and can be stored at room temperature. They are a useful modality to combat COVID-19, especially in remote and low resource settings.